Commentary on: Xbp1s-Ddit3, DNA damage and pulmonary hypertension. Issue 1 (14th January 2022) - Lemay, Sarah-Eve; Bonnet, Sebastien; Potus, François
Abstract: In this commentary, we discuss new observations stating that spliced X-box-binding protein 1 (Xbp1s)-DNA damage-inducible transcript 3 (Ddit3) promotes monocrotaline (MCT)-induced pulmonary hypertension (Jiang et al., Clinical Science (2021) 135 (21), https://doi.org/10.1042/CS20210612 ). Xbp1s-Ddit3 is involved in the regulation of endoplasmic reticulum stress but is also associated with DNA damage repair machinery. Pathologic DNA damage repair mechanisms have emerged as critical determinants of pulmonary hypertension development. We discuss the potential relationship among Xbp1s-Ddit3, DNA damage, and pulmonary hypertension. Although Xbp1s-Ddit3 contributes to the regulation of cell proliferation and apoptosis and the development of vascular lesions, whether Xbp1s is a friend or foe remains controversial.